Perancangan Alat Penentuan Koefisien Gesek Statis Menggunakan Sensor IR FC-51 dan Potensiometer Berbasis Arduino Uno - Manuhutu, Fredrik; Kesaulya, Noke; Rachman, Gazali (Physikos: Journal of Physics and Physics Education, 2023)
An Arduino Uno-based static friction coefficient (µs) determination tool equipped with an IR sensor module FC-51 has been created. This µs determination tool is made to reduce the possibility of observation errors when doing physics labs. The µs determination tool consists of an FC-51 IR sensor component to detect precisely when an object is moving. The potentiometer measures the angle of the base surface, and an Arduino Uno device transmits data from the hardware to the computer in real time. The work test of the µs determination tool starts with the base surface with a slope of 0o, and then the object is placed on the base surface and precisely above the surface of the FC-51 IR sensor. When the base surface is tilted slowly, the potentiometer also rotates, showing the plane angle's size. As long as the object is not moving, the IR FC-51 sensor is in low condition. When the object moves, the IR FC-51 sensor is in high condition. The change in signal from low to high indicates that the object is moving when the plane reaches the slope angle, and the slope angle shows the value of µs. The µs are measured on a wooden base with wooden blocks and a glass base with glass blocks. The results obtained for a wooden base with wooden blocks µs = 0.73 with an average slope angle = 36.16o and a glass base with glass blocks µs = 0.4 with an average slope angle = 22.1o. The results show that the µs level of the wood surface with wood is greater than the µs level of the glass surface with glass.